The Influence of High Performance Work System, Burnout on Intention to Leave with Mentoring as a Moderating Variable (International Journal of Scientific Research and Management (IJSRM), 2024)
Introduction: The Covid-2019 pandemic has had a negative impact on burnout and at the same time employee job satisfaction has become a benchmark for intentions to leave. Challenges in human resource management for health workers are experiencing very rapid changes which result in demand for nursing staff, community socio-economic conditions, declining family health status, and increasing public awareness. HPWS as a tool for identifying employee productivity with comprehensive training/mentoring contributes to new performance challenges. Fatigue and stopping work is a threat to companies. The aim of this research is to analyze the role of HPWS on intention to leave (ITL) with mentoring as a moderator and burnout as a mediator. Method : Quantitative research method with survey method using primary data in the form of questionnaires distributed to health workers who handle Covid-19 at private hospitals in Kab. Ponorogo. The sampling technique used simple random sampling with a sample size of 162 people. Hypothesis testing using Structural Equation Modeling (SEM)-PLS analysis with WarpPLS 7.0. Results : The research results show that HPWS has an influence on burnout and through mentoring moderation, HPWS has an influence on intention to leave, job satisfaction influences ITL with a significant difference (p<0.05). Conclusion : These findings aim to determine the effect of HPWS on burnout, job satisfaction, Intention to Leave through mentoring before burnout occurs and after burnout occurs. These findings can help identify the influence of HPWS on intention to leave.